KAJIAN POTENSI DAN PENGEMBANGAN TURBIN ANGIN DAERAH URBAN - Nurdin, Akhmad (Politeknik Harapan Bersama Tegal, 2022)
In urban areas, wind turbines can be integrated into buildings or called building integrated wind turbines. On the other hand, wind patterns in urban areas are turbulent and have more complex problems. The wind characteristics of a region are different, this is influenced by ground surface conditions. Conditions of high roughness length values, such as urban areas, create a large turbulent zone, besides that at the same time the wind pound buildings and other objects, causing a wind vortex profile. This study discusses the characteristics of the wind and the feasibility of the potential application of wind turbines in urban or urban areas. The purpose of this study was to discuss the phenomenon and potential of wind in urban areas and to review several studies on the application of wind turbines in urban areas.